Overexpression of MtDof32 in Medicago truncatula enhances leaf and flower organ size through modulation of cell expansion - Guo, Tao; Wang, Huan; Wang, Shumin; Zhou, Ling; Sui, Shunzhao (Frontiers in Plant Science, 2025)
As leaf organ size is a key determinant of plant morphology and development, elucidating the cellular and molecular mechanisms governing organ size regulation has become a central research focus in legume biology. DNA binding with one finger 32 (MtDof32), previously identified as a key regulatory factor in organ development, has been shown to influence leaf and flower organ size in Arabidopsis. Here, we demonstrated that MtDof32 overexpression in Medicago truncatula resulted in the enlargement of both leaf and flower organs. Cellular analysis revealed that MtDof32 primarily modulated organ size by controlling cell expansion. Yeast two-hybrid, co-immunoprecipitation (Co-IP), and bimolecular fluorescence complementation (BiFC) assays collectively established the nuclear-localized interaction between MtDof32 and MtEBP1. Additionally, we observed that MtDof32 overexpression led to delayed flowering and reduced branching in transgenic plants. Comparative analysis with wild-type plants indicated significant alterations in the expression levels of key flowering and branching regulatory genes. This study underscored the conserved role of MtDof32 in regulating organ size across leguminous species, offering valuable insights for the genetic modification and utilization of this gene in crop improvement strategies.